PERFORMANCE STUDY OF MOVING BIOFILM AEROBIC SEQUENCING BATCH REACTOR (MBASBR) FOR THE TREATMENT OF PAPER AND PULP MILL EFFLUENT - kumar R, Ranjith; K, Subramanian (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In this study the experiments are conducted to remove the Chemical oxygen demand (COD),Total suspended solids (TSS) and Lignin from paper and pulp mill wastewater using Moving biofilm aerobic sequencing batch reactor (MBASBR) .The laboratory scale reactor of working volume 20 liters used for the study. In addition to the conventional reactor the plastic carrier is used as the moving biomedia for the suspended and attached growth treatment in the reactor. Microbial culture of Phenerochetes chrysosporium and Pseudomonas alcaligens is used for the treatment. These microbes show good attachment with the carrier for the biochemical degradation of the paper and pulp mill wastewater during the treatment process. The average removal efficiencies for COD, TSS and lignin are found to be 96%, 98% and 84 % respectively.